1987
DOI: 10.2465/ganko1941.82.319
|View full text |Cite
|
Sign up to set email alerts
|

Ultramafic rocks in the Kurosegawa tectonic zone, Southwest Japan.

Abstract: The Kurosegawa tectonic zone extends from Kyushu to the western Kii Peninsula and con tains ultramafic rocks with two distinct textural and chemical types of olivine and clinopyroxene. The ultramafic bodies were mainly harzburgites or lherzolites which originally equilibrated at around amphibolite facies conditions and subsequently re-equilibrated near 400•Ž. Ultramafic rocks in the Chichibu belt, from the eastern Kii Peninsula to the Kanto Mountains, have the same textural and chemical characteristics as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Several brief petrological descriptions of the Mikame ultramafic rocks were given by Ishimoto (1973), Suzuki (1977), and Yokoyama (1987). They reported that the Mikame ultramafic rocks are predominantly dunite and wehrlite, with minor amounts of harzburgite, lherzolite, websterite, and orthopyroxenite.…”
Section: Geological Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…Several brief petrological descriptions of the Mikame ultramafic rocks were given by Ishimoto (1973), Suzuki (1977), and Yokoyama (1987). They reported that the Mikame ultramafic rocks are predominantly dunite and wehrlite, with minor amounts of harzburgite, lherzolite, websterite, and orthopyroxenite.…”
Section: Geological Outlinementioning
confidence: 99%
“…The isotherm curves are from Obata et al (1974). For comparison, the plots of the serpentinites from the Mariana forearc (Murata et al 2009) and the Kurosegawa belt (Yokoyama, 1987) are also shown. The symbols are the same as those in Figure 4.…”
Section: Sub-solidus Equilibriamentioning
confidence: 99%
See 1 more Smart Citation
“…Serpentinite A: olivine-bearing serpentinite mylonite from the Toba area Lenticular serpentinite bodies intrude a Jurassic accretionary complex and pre-Cretaceous metamorphic rocks in the Toba area, southwest Japan (Fig. 1a) (Saka et al, 1988;Yokoyama, 1987). Occasionally, the serpentinite body contains blocks of schists that have undergone highpressure metamorphism (Saka et al, 1988).…”
Section: Samplesmentioning
confidence: 99%
“…Veins consist mainly of olivine with lesser diopside, magnetite, and antigorite. Yokoyama (1987) estimated the temperature of vein formation as 400°C, based on the Mg-Fe equilibrium in olivine-clinopyroxene assemblages.…”
Section: Samplesmentioning
confidence: 99%